TEMPERATURE CONTROL OF THERMOELECTRIC MODULES IN COGENERATION PLANTS - Rutylo М. (Energy and Automation, 2016)
The necessity of creation of control modes of thermoelectric modules in heating generators cogeneration units. The algorithm for determining the temperature of the hot surface of the module for its electrical parameters. Created a simulation model of control system of thermoelectric module modes based on the proposed algorithm.